Analisis Keanekaragaman Flora dan Fauna di Hutan Mangrove, Kelurahan Bagan Barat, Kabupaten Rokan Hilir - Hanifah Ikhsani; Anesha Allasselcida; Dinda Tri Agustina; Erwanda Trio Bintan Sabri; Maryani Maryani (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2026)
This study aims to analyze the diversity of flora and fauna in the mangrove forest of Bagan Barat Village, Rokan Hilir Regency. The research was conducted using a combination of transect and nested sampling methods to assess vegetation structure at different growth levels, including trees, poles, saplings, and seedlings, while fauna observations were carried out through direct and indirect approaches. The results showed that the mangrove ecosystem is dominated by three main species, namely Avicennia marina, Avicennia alba, and Acanthus ilicifolius. The Shannon-Wiener diversity index of flora at all growth levels ranged from moderate to relatively high, indicating a fairly stable ecosystem, although species composition remains limited and dominated by Avicennia marina. The Simpson dominance index at the tree level indicated moderate dominance, while the evenness index showed low distribution among species. A total of 15 fauna species were identified, consisting of reptiles, birds, mammals, arthropods, and fish. The fauna diversity index was categorized as moderate to high, with relatively high evenness and low dominance, reflecting a balanced community structure. Overall, the mangrove ecosystem in the study area has a moderate level of biodiversity and stability, but efforts to increase species diversity are needed to support sustainable ecosystem management.